Modeling the middle Pliocene climate with a global atmospheric general circulation model - Jiang, Dabang; Wang, Huijun; Ding, Zhongli; Lang, Xianmei; Drange, Helge (Journal of Geophysical Research: Atmospheres, 2005)
A new climate simulation for the middle Pliocene (ca. 3 Ma BP) is performed by a global grid-point atmospheric general circulation model developed at the Institute of Atmospheric Physics (IAP AGCM) with boundary conditions provided by the U. S. Geological Survey's Pliocene Research, Interpretations, and Synoptic Mapping (PRISM) group. It follows that warmer and slightly wetter conditions dominated at the middle Pliocene with a globally annual mean surface temperature increase of 2.60°C, and an increase in precipitation of 4.0% relative to today. At the middle Pliocene, globally annual terrestrial warming was 1.86°C, with stronger warming toward high latitudes. Annual precipitation enhanced notably at high latitudes, with the augment reaching 33.5% (32.5%) of the present value at 60–90°N (60–90°S). On the contrary, drier conditions were registered over most parts at 0–30°N, especially in much of East Asia and the northern tropical Pacific. In addition, both boreal summer and winter monsoon significantly decreased in East Asia at the middle Pliocene. It is indicated that the IAP AGCM simulation is generally consistent with the results from other atmospheric models and agrees well with available paleoclimatic reconstructions in East Asia. Additionally, it is further revealed that the PRISM warmer sea surface temperature and reduced sea ice extent are main factors determining the middle Pliocene climate. The simulated climatic responses arising from the PRISM reconstructed vegetation and continental ice sheet cannot be neglected on a regional scale at mid to high latitudes (like over Greenland and the Qinghai-Tibetan Plateau, and around the circum-Antarctic) but have little influence on global climate.
Keywords: Antarktis; global klimamodell; global oppvarming; innlandsis; paleoklimatologi; polarområdene

Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

A multi-proxy approach to determine Antarctic terrestrial palaeoclimate during the Late Cretaceous and Early Tertiary - Poole, Imogen; Cantrill, David; Utescher, Torsten (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Fossil wood is abundant throughout the Cretaceous and Tertiary sequences of the northern Antarctic Peninsula region. The fossil wood represents the remains of the vegetation that once grew at the southern high palaeolatitudes at 59–62°S through the general decline in climate, from the Late Cretaceous global warmth through to the mid-Eocene cool period prior to the onset of glaciation. This study draws on the largest dataset ever compiled of Antarctic conifer and angiosperm woods in order to derive clearer insights into the palaeoclimate. Parameters including mean annual temperature, mean annual range in temperature, cold month mean, warm month mean, mean annual precipitation are recorded. The fossil wood assemblages have been analysed using anatomical (physiognomic) characteristics to determine the palaeoclimate variables from the Coniacian–Campanian to the middle Eocene. These results are compared with data derived from Coexistence Analysis of the fossil floras (composed of leaves, wood and palynomorphs) and published data based on leaf physiognomic characters. These studies indicate a relatively warm and wet Late Cretaceous that becomes drier and cooler in the Early Paleocene and subsequently returns to warmer, wetter conditions by the latest Early Paleocene. During the Eocene the climate becomes relatively cool and dry once again. The discrepancies obtained from these two methods coupled with other published data are discussed in the context of the fluctuations in the temperatures of the surrounding oceans and global patterns of climate change.
Keywords: Antarktis; paleobotanikk; paleogeografi; paleoklimatologi; paleontologi

Holocene climate evolution in the high-latitude Southern Hemisphere simulated by a coupled atmosphere-sea ice-ocean-vegetation model - Renssen, Hans; Goosse, Hugues; Fichefet, Thierry; Masson-Delmotte, Valérie; Koç, Nalân (Holocene, 2005)
The Holocene climate is simulated in a 9000-yr-long transient experiment performed with the ECBilt-CLIO-VECODE coupled atmosphere-sea ice-ocean-vegetation model. This experiment is forced with annually varying orbital parameters and atmospheric concentrations of CO2 and CH4. The objective is to study the impact of these long-term forcings on the surface temperature evolution during different seasons in the high-latitude Southern Hemisphere. We find in summer a thermal optimum in the midHolocene (6-3 ka BP), with temperatures locally 3°C above the preindustrial mean. In autumn the temperatures experienced a long-term increase, particularly during the first few thousand years. The opposite trend was simulated for winter and spring, with a relatively warm Southern Ocean at 9 ka BP in winter (up to 3.5°C above the preindustrial mean) and a warm continent in spring (+3°C), followed by a gradual cooling towards the present. These long-term temperature trends can be explained by a combination of (1) a delayed response to orbital forcing, with temperatures lagging insolation by 1 to 2 months owing to the thermal inertia of the system, and (2) the long memory of the Southern Ocean. This long memory is related to the storage of the warm late winter-spring anomaly below the shallower summer mixed layer until next winter. Sea ice plays an important role as an amplifying factor through the ice-albedo and ice-insulation feedbacks. Our experiments can help to improve our understanding of the Holocene signal in proxies. For instance, the results suggest that, in contrast to recent propositions, teleconnections to the Northern Hemisphere appear not necessarily to explain the history of Southern Hemisphere temperature changes during the Holocene.
Keywords: Sørishavet; holocene; klimaendringer; klimamodeller; paleoklimatologi